The Effect of Shopping Life Style and Positive Emotion on Buying Impulse (Case Study of the Palembang City Hypermarket) - Maulana, Ahmad; ., Mukhlis; Novalia, Nurkardina (Information Management and Business Review, 2019)
This study aims to determine: (1) the effect of Shopping Life Style on impulse buying on customers at Palembang City Hypermarket, (2) the effect of positive emotions on Impulse buying on customers at Palembang City Hypermarket, (3) the effect of Shopping Life Style and positive emotions impulse buying for customers at the Palembang City Hypermarket. This study uses primary data obtained by survey methods by distributing questionnaires that have been tested for validity and reliability. The population in this study were customers at the Palembang City Hypermarket. The sampling technique used purposive sampling method with a total sample of 150 people. The data analysis technique used is path analysis. Shopping LifeStyle has a significant effect on the Hypermarket impulse buying in Palembang. Positive emotions have a significant effect on Impulse Buying at Hypermarket consumers in Palembang.